Effect of gastrointestinal heat retention syndrome on gut microbiota in children with upper respiratory tract infection and lung-heat syndrome - Shuangcheng Wang; Xueyan Ma; Liqun Wu; He Yu; Yanran Shan; Yuanshuo Tian; Tiegang Liu; Xiaohong Gu (Journal of Traditional Chinese Medical Sciences, 2022)
Objective: Gastrointestinal heat retention syndrome (GHRS) is associated with lung-heat syndrome and is related to recurrent respiratory infection. Upper respiratory tract infection (URTI) lung heat syndrome is common in children. The study will explore the effect of GHRS on the structure and function of gut microbiota in children with URTI lung-heat syndrome. Methods: Participants were divided into both groups using the self-developed URTI scale and the “GHRS Diagnostic Scale · Pediatric Part”: GHRS-positive children (LS group) and GHRS-negative children (L group). General information, clinical symptoms, and stool were collected. We used 16S rRNA amplicon sequencing technology to determine the gene sequence of the V3–V4 region in feces and measure the gut microbiota of the both groups at the genus level. Results: A total of 23 children were included in the both groups. There were 12 cases in the LS group and 11 cases in the L group. There was no statistical difference between the both groups in age, gender, height, weight, and body mass index. The effective sequences shared by the both groups accounted for 85.66% of the total. In the gut microbiota, there was no difference in the α diversity and the β diversity between the both groups. Compared with the L group, the LS group had a significant increase in the relative abundance of the Ruminococcus gnavus group, Prevotella-9, Staphylococcus, and Actinomyces (P < .05). The functions of the both groups of microbiota primarily concentrate on metabolism, genetic information processing, and environmental information processing. The relative abundance of signaling molecules and interactions in the LS group were higher than that in the L group (P < .05). The redundancy analysis (RDA) showed that the URTI score had the greatest impact on the distribution of microbiota. Conclusion: GHRS may affect the development of URTI lung-heat syndrome by changing the relative abundances of gut microbiota.